Marking the Queen's Platinum Jubilee. (3rd June 2022) - Ryan, Mandy
Abstract: BVA is fortunate to have the Queen as our royal patron. Mandy Ryan, BVA's head of media, outlines our plans for congratulating her and celebrating her 70‐year reign.